The Effect of Variation in the Composition of Candlenut Shell Charcoal Powder/Epoksi Composite on Hardness Value, Friction Coefficient and Specific Wear Rate - Pratiwi, Putri; Nurzal, Nurzal; Syaifullah, Muhammad; Perdana, Mastariyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
Organic waste processing by utilizing the candlenut shell charcoal has great potential to produce useful materials. The large seed and skin ratio makes candlenut shells very abundant during the harvest season. Candlenut shells are known as agricultural waste even though they have great potential to be utilized because of their good mechanical properties. The purpose of this study was to determine the effect of composition variations in candlenut shell charcoal powder composites on their mechanical properties such as hardness values, friction coefficients and wear rates. The materials used are candlenut shell charcoal powder and epoxy, with a fraction ratio of 55%: 45% wt, 60%: 40% wt, 65%: 35% wt, 70%: 30% wt, 75%: 25% wt, 80%: 20% wt, 85% : 15% wt. The size of the candlenut shell charcoal powder used is 841-1190 μm. The results of the study showed the highest hardness of 74.94 HRN, a wear value of 0,000077407407 g/mm2, and the friction coefficient of 0.2108.